Top 5 parasites in Africa - Daka, David (Запорізький державний медичний університет, 2015)
Parasitic infection is one of the ten top major public health problems in developing African countries. Children being major victims, therefore analysis of distribution, effective prevention and control of parasitic infections require the identification of local risk factors, particularly among high risk groups. The aim of the study. To analyze prevalence of parasitic diseases in Africa.